2009
DOI: 10.1007/s11418-009-0360-6
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant properties of bioactive fractions from the extract of Crocus sativus L.

Abstract: The aim of this study was to investigate the antidepressant properties of stigmas and corms of Crocus sativus L. The aqueous ethanol extract of C. sativus corms was fractionated on the basis of polarity. Among the different fractions, the petroleum ether fraction and dichloromethane fraction at doses of 150, 300, and 600 mg/kg showed significant antidepressant-like activities in dose-dependent manners, by means of behavioral models of depression. The immobility time in the forced swimming test and tail suspend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 21 publications
3
94
0
2
Order By: Relevance
“…Previous studies have already demonstrated that the ethanol extracts of saffron petal has antidepressant effect in a pre-clinical study (Moshiri et al, 2006), and petroleum ether and dichloromethane fractions of saffron corms produce antidepressant-like effects in behavioral models predictive of antidepressant properties (Wang et al, 2010). It is also reported that a kind of glucoconjugate, isolated from saffron corms and calluses has cytotoxic activity property against tumor cells (Escribano et al, 2000).…”
Section: Research Articlementioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have already demonstrated that the ethanol extracts of saffron petal has antidepressant effect in a pre-clinical study (Moshiri et al, 2006), and petroleum ether and dichloromethane fractions of saffron corms produce antidepressant-like effects in behavioral models predictive of antidepressant properties (Wang et al, 2010). It is also reported that a kind of glucoconjugate, isolated from saffron corms and calluses has cytotoxic activity property against tumor cells (Escribano et al, 2000).…”
Section: Research Articlementioning
confidence: 97%
“…Moreover, saffron stigma has been used as a drug in folk medicine since ancient times for various purposes such as an aphrodisiac, antispasmodic, andexpectorant, antidepressant, and stomachic agent (Abdullaev, 1993;Richelson, 1994;Wang et al, 2010). In some folk remedies, it was also used against scarlet fever, smallpox, colds, asthma, eye, and heart diseases (Rios et al, 1996;Abdullaev and EspinosaAguirre, 2004;Carmona et al, 2007;Nemati et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Saffron (Crocus sativus L.) is a traditional therapeutic agent (11) mental, and cardiovascular disorders; moreover, it is used as an analgesic and antiinflammatory agent (12). Recent experimental and clinical findings indicate that saffron may have potentials in the treatment of mild to moderate depression, as well as some sexual problems (13)(14)(15)(16). The main carotenoid in saffron, crocin, seems to be responsible for its beneficial effects on mental and sexual health (14,17).…”
Section: Introductionmentioning
confidence: 99%
“…(Iridaceae), commonly known as saffron, is a perennial stemless plant. Saffron stigma has become more and more popular due to its versatile biological and medicinal properties, such as anaphrodisiac, antispasmodic, expectorant, antidepressant, and stomachic activity (Abdullaev, 1993;Richelson, 1994;Wang et al, 2010). However, high demand but low yield resulted in extreme scarcity of this valuable medicinal resource.…”
Section: Introductionmentioning
confidence: 99%